Drug-like antagonists of P2Y receptors — from lead identification to drug development - Conroy, Sean; Kindon, Nicholas; Kellam, Barrie; Stocks, Michael (American Chemical Society, 2016)
P2Y receptors are expressed in virtually all cells and tissue types and mediate an astonishing array of biological functions, including platelet aggregation, smooth muscle cell proliferation, and immune regulation. The P2Y receptors belong to the G protein-coupled receptor superfamily and are composed of eight members encoded by distinct genes that can be subdivided into two groups on the basis of their coupling to specific G-proteins. Extensive research has been undertaken to find modulators of P2Y receptors, although to date only a limited number of small-molecule P2Y receptor antagonists have been approved by drug/medicines agencies. This Perspective reviews the known P2Y receptor antagonists, highlighting oral drug-like receptor antagonists, and considers future opportunities for the development of small molecules for clinical evaluation.